Bratton's Idea - Wellman, Manly Wade, 1903-1986; Giunta, John, 1920-1970 (Salt Lake City, UT : Project Gutenberg, 2021)
"Bratton's Idea" by Manly Wade Wellman is a short story written in the early 20th century, likely during the mid-1900s, that intertwines elements of science fiction with dark comedy. The narrative centers around an aging janitor named Old Bratton, who is obsessed with creating life through electricity. His ambitions and experiments take an unexpected turn when he acquires a ventriloquist's dummy, Tom-Tom, and infuses it with life through his mechanical inventions, leading to a series of chaotic and dangerous events in the world of show business and organized crime. In the story, Old Bratton's endeavors to animate Tom-Tom result in unintended consequences when the dummy gains a twisted form of sentience. As Tom-Tom embarks on a crime spree after Bratton's death, he wields his unwitting abilities to command a gang and orchestrate kidnappings, including that of the beautiful Shannon Cole. The tale unfolds with Ben Gascon, a ventriloquist, trying to uncover the connection between his former partner, Bratton, and Tom-Tom's sudden malevolence. As a cat-and-mouse game ensues between Gascon and the doll, the story explores themes of creation, ambition, and the darker sides of sentience, culminating in a climactic confrontation where the true nature of life and morality is sharply questioned. (This is an automatically generated summary.)
Release date is 2021-03-11
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Man-woman relationships -- Fiction; Robots -- Fiction; Inventions -- Fiction; Los Angeles (Calif.) -- Fiction